2021
DOI: 10.1017/s0954102021000420
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts from the Maritime Antarctic: tools for industry and bioremediation

Abstract: We isolated 32 yeasts from King George Island, which we then identified and characterized. Twenty-six belonged to Basidiomycota among the genera Naganishia, Holtermaniella, Vishniacozyma, Phenoliferia, Mrakia and Cystobasidium, and only six were Ascomycota of the genera Metschnikowia and Debaryomyces. Thirteen were psychrophiles, while 19 were psychrotolerant. Certain isolates exhibited a high tolerance to NaCl (3.5 M), while most tolerated Ni2+, Zn2+ and Li+. Cu2+ and Cd2+, however, inhibited the growth of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, to date only two surveys related to Antarctic yeasts and their potential in dye removal have been reported: The first was conducted by Rovati et al ( 2013 ), who found that 33 percent of 61 yeasts isolated from King George Island were capable of removing a mixture of four dyes in solid medium at a final concentration of 200 mg L –1 between 10 to 20 days of culture at 15 °C. The second was performed by Bezus et al ( 2021 ) who reported that 32 psychrophilic and psychrotolerant yeast isolates were able to remove at least one of the dyes used (RO-16, RB-5, and RB-19).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, to date only two surveys related to Antarctic yeasts and their potential in dye removal have been reported: The first was conducted by Rovati et al ( 2013 ), who found that 33 percent of 61 yeasts isolated from King George Island were capable of removing a mixture of four dyes in solid medium at a final concentration of 200 mg L –1 between 10 to 20 days of culture at 15 °C. The second was performed by Bezus et al ( 2021 ) who reported that 32 psychrophilic and psychrotolerant yeast isolates were able to remove at least one of the dyes used (RO-16, RB-5, and RB-19).…”
Section: Resultsmentioning
confidence: 99%